Can education as an ‘International Commodity’ be the backbone or cane of a nation in the era of fourth industrial revolution? - a comparative study - Alam, Gazi Mahabubul; Forhad, Abdur Rahman; Ismail, Ismi Arif (Elsevier, 2020)
Governments of developing nations and ‘development partners’ consider education as an ‘international product’ that makes economic advancement possible. Hence, education in developing nations is always sluggish in responding to the changes of contemporary concepts. The fourth industrial revolution is a concept that explains the latest stage of economic development. When many developed countries’ education systems are still struggling to cope with this concept, developing countries want to copy them. Thus, the question can be asked: can a copied ‘international product’ necessarily support the ‘national development’ or ultimately assist ‘international development’? Using philosophical debates as a metaphor, some studies have attempted to answer. In the era of globalization, foreign income is the most important element of national development. This comparative study is the first to investigate the influence of education in earning foreign income. Multi-national data collected by designated agencies from both developed and developing nations are used. Findings show that quantitative and qualitative indicators of education in developing countries are figuratively catching up with the advanced economies. Certain industries need highly skilled individuals to grow the amount of a nation's foreign income. Education systems in developed counterparts are able to produce skilled graduates who contribute significantly for foreign income. For developing economies, foreign income mainly depends on low-skilled industry sectors. Education in developing countries is discussed here in terms of ‘Dependency Theory’.